The Mesentery and Inflammation - Coffey, J. Calvin (Cham : Springer International Publishing : Imprint: Springer, 2023)
The volume summarizes the most recent advances in our understanding of the mesentery and explains the how these are important in inflammation. It comprises a series of state of the art chapters by leading authorities in each area. It explains how recent advances in our understanding of the mesenteric organ, have advanced the diagnosis and treatment abdominal and systemic conditions including cancer, inflammatory bowel disease and endocrine conditions such as diabetes, and circulatory disorders such as atherosclerosis. .
Introduction -- Development, anatomy and histology of the mesentery -- The mesenteric intersitium -- Mesnteric organ lymphatics -- The mesentery as an immunological organ -- Bacterial translocation to the mesentery -- The microbiome of mesenteric lymh nodes -- Mesenteric Adenopathy and adenitis -- The effects of mesenteric inflammation on the intestine -- The mesentery as an ADME organ -- Targteing the mesentery using surgery -- Future directions.
Keywords: Pharmacology; Neurosciences; Psychiatry; Medical genetics; Clinical health psychology; Human physiology; Pharmacology; Neuroscience; Psychiatry; Medical Genetics; Health Psychology; Human Physiology